2015
DOI: 10.1177/0160449x15619539
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Effects of Adopting a Right-to-Work Law

Abstract: While considerable efforts have been made by legislators, business associations, and political organizations to pass right-to-work (RTW) laws in states across the country, the empirical evidence on the effect of adopting an RTW law on labor market outcomes and state budgets is both varied and mixed. This article provides a forecast on the effect of RTW laws on important labor market outcomes-including earnings, employment, unionization, and inequality. It also investigates RTW's impacts on two particularly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Concern about simultaneity bias was often addressed (Warren and Strauss 1979;Wessels 1981;Farber 1984;Koeller 1985;Moore et al 1986; Davis and 1 Right-to-work potentially affects a number of outcomes beyond the rate of unionization. Outcomes studied in previous work include manufacturing activity (Holmes 1998), stockholder wealth (Abraham and Voos 2000), earnings (Reed 2003;Farber 2005;Gould and Shierholz 2011;Bruno, Zullo, Manzo, and Dickson 2015;Gould and Kimball 2015), business conditions (Stevans 2009), and union finances and political outcomes (Feigenbaum, Hertel-Fernandez, and Williamson 2019).…”
Section: Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Concern about simultaneity bias was often addressed (Warren and Strauss 1979;Wessels 1981;Farber 1984;Koeller 1985;Moore et al 1986; Davis and 1 Right-to-work potentially affects a number of outcomes beyond the rate of unionization. Outcomes studied in previous work include manufacturing activity (Holmes 1998), stockholder wealth (Abraham and Voos 2000), earnings (Reed 2003;Farber 2005;Gould and Shierholz 2011;Bruno, Zullo, Manzo, and Dickson 2015;Gould and Kimball 2015), business conditions (Stevans 2009), and union finances and political outcomes (Feigenbaum, Hertel-Fernandez, and Williamson 2019).…”
Section: Previous Literaturementioning
confidence: 99%
“…More recent work on the RTW effect pays closer attention to identification strategy (Dinlersoz and Hernandez-Murillo 2002; Bruno et al 2015; Eren and Ozbeklik 2016; and Manzo and Bruno 2017). Dinlersoz and Hernandez-Murillo (2002) compared Idaho, which adopted right-to-work in 1986, to six neighboring states and found that the trend in union membership in Idaho following adoption did not differ from the trends in neighboring states.…”
Section: Previous Literaturementioning
confidence: 99%
“…Moreover, SEIU HCIIMK would have likely been financially affected by the passage of RTW laws elsewhere in the Midwest states they represent (i.e., Indiana and Missouri; Kansas has been RTW since 1958) because of the financial interlock with its affiliates in surrounding states. In the 2010s, after the Republican Party gained power in a number of Midwestern state legislatures and governorships, it introduced a round of initiatives to pass RTW laws partially as a response to the global financial crisis (Bruno et al 2015; Devinatz 2011). Concurrently during our sample time period, coordinated networks of right-wing activists, led by groups like the American Legislative Exchange Council (ALEC) and supported by right-wing media, pushed for the passage of RTW legislation throughout the region (DiGrazia and Dixon 2020).…”
Section: Canvassing Under Political Constraintsmentioning
confidence: 99%
“…As a result, Indiana, Michigan, and Wisconsin sequentially passed such laws. 3 Because RTW financially constrains unions within these states from contributing to political campaigns and mobilizing members (Bruno et al 2015; Feigenbaum, Hertel-Fernandez, and Williamson 2018), SEIU HCIIMK would have needed to engage in financial solidarity with its affiliates within these states to ensure their financial stability (Finger and Hartney 2021). In sum, although SEIU HCIIMK is headquartered in a relatively prolabor environment without its own RTW regime, its ability to support political canvassing would have been constrained by the union's financial interlocks spanning other RTW states, as well as the anti-union principles espoused by then-governor Rauner.…”
Section: Canvassing Under Political Constraintsmentioning
confidence: 99%
“…Researchers have used difference‐in‐differences (Bruno et al. ), propensity score matching (Roberts and Habans ), and synthetic control methods (Eren and Ozbeklik ) to estimate the effects of RTW laws. Still, the results have been mixed: on the high end, propensity score matching has found RTW to be associated with a wage penalty of approximately 6 percent (Roberts and Habans ).…”
Section: Relation To the Literature On Collective Bargaining Law And mentioning
confidence: 99%